Membangun Citra Melalui Kolaborasi: Studi Co-Branding dan Brand Experience Mobile Legends dan Attack on Titan - Poetry, Salfhaoctha Friemay Aliefia; Nurjanah, Anna; Irawan, Novida (CV. ITTC INDONESIA, 2025)
Currently, there are few studies that examine how marketing strategies such as co-branding and brand experience affect corporate image in the context of the gaming industry. Most previous studies have focused on the impact of co-branding on sales or brand awareness without exploring its influence on corporate reputation. This study aims to analyze the influence of co-branding strategy and brand experience on the corporate image of PT Monster Entertainment Indonesia in the context of the Mobile Legends and Attack on Titan collaboration. In the digital age, collaboration-based marketing strategies are becoming increasingly important in increasing brand appeal and building relationships with audiences. This study uses a quantitative approach with a survey method of 100 respondents, which is obtained through probability sampling techniques. The results show that co-branding has a significant and more dominant influence on the company's image than brand experience, with a β coefficient value of 0.432. Meanwhile, brand experience also contributes positively to the company's image, albeit with a smaller influence (β = 0.312). These findings indicate that collaborations with popular brands, such as Attack on Titan, can reinforce a positive perception of the company in the eyes of the public. Regression analysis showed that these two variables together explained 60.3% of the variability in the company's image, while the remaining 39.7% was influenced by other factors outside the study. Thus, collaboration-based marketing strategies and innovative brand experiences can be an effective step for companies in improving their image and competitiveness in the gaming industry